Christian communities and intimate partner violence in sub-Saharan Africa: A scoping review - Stiles-Ocran, Elorm A. (HTS teologiese studies, 2025)
Intimate partner violence (IPV) is a growing development concern affecting women globally including sub-Saharan Africa (SSA). However, knowledge of the involvement of Christian faith communities with IPV and their work on the empowerment of survivors of IPV in SSA is currently vague. The aim of this scoping study was to provide an overview of documented studies conducted in this area as well as identify possible gaps for empirical research. The authors employed a six-step strategy for scoping studies. The search strategies involved electronic searches in nine databases and academic search engines between 11 September 2021 to 23 January 2024. Manual searches in bibliographies were also carried out for grey literature, and one additional study was recommended by stakeholders in consultation with them. The selected studies were analysed for themes and patterns in relation to the research questions and aims. Findings indicate a growing interest in this field of research over the past few years. However, there is inadequate representative knowledge of IPV in SSA and how Christian faith communities deal with it. It is also striking that colonialism and post-colonialism are hardly mentioned in the reviewed research work. From the analysis, it is obvious that faith communities and faith leaders have the potential to fight IPV.Contribution: The article highlights the areas within the important research field of religion and IPV that have been explored in SSA, as well as the significant gaps that remain. It emphasises the need for multidisciplinary and interconnected approaches to address these gaps.